A proposed set of exercises on inference-making for college students in technical schools - Fonacier, Erlinda Ravelo 1931- (1977)
This set of Reading for Comprehension exercises drawn from local and foreign sources consists of eighty items of various graded reading difficulty. This was designed to aid the freshmen, particularly technical students in developing and improving their inferential reading ability. The study included the compilation, construction, item analysis, and experimental try-out of the whole set on the different curriculum levels, particularly fourth year high school, first and second years technical and professional students. The items were tried on students in northwestern Cagayan. The results of the RFU items gave a moderately high result despite the poorly printed material.